2018
DOI: 10.1371/journal.pgen.1007442
|View full text |Cite
|
Sign up to set email alerts
|

The bithorax complex iab-7 Polycomb response element has a novel role in the functioning of the Fab-7 chromatin boundary

Abstract: Expression of the three bithorax complex homeotic genes is orchestrated by nine parasegment-specific regulatory domains. Autonomy of each domain is conferred by boundary elements (insulators). Here, we have used an in situ replacement strategy to reanalyze the sequences required for the functioning of one of the best-characterized fly boundaries, Fab-7. It was initially identified by a deletion, Fab-71, that transformed parasegment (PS) 11 into a duplicate copy of PS12. Fab-71 deleted four nuclease hypersensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…Binding Sites for the Architectural Proteins Cooperate with dHS1 in Organization of the Functional Boundary. We previously found that the distal 240 bp of the HS1 region (dHS1) is critical for the boundary activity of Fab-7 and contains the LBC recognition sequences (38,44,46). However, dHS1 alone has only some residual boundary function (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding Sites for the Architectural Proteins Cooperate with dHS1 in Organization of the Functional Boundary. We previously found that the distal 240 bp of the HS1 region (dHS1) is critical for the boundary activity of Fab-7 and contains the LBC recognition sequences (38,44,46). However, dHS1 alone has only some residual boundary function (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since dHS1 is bound by LBC in nuclear extracts, an important question is whether LBC is responsible (at least in part) for the bypass activity of this sequence in vivo. The minimal Fab-7 recognition sequence binding this very large complex was ∼65 bp long (38,46). Although the GAGAG motifs in the small 65-bp probes are critical for LBC binding, they are less important when larger dHS1 sequences are used for EMSA probes, because neighboring sequences may contain additional binding sites for proteins that stabilize LBC recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, as in vertebrates, dCTCF is one of dozens of polydactyl C2H2 zinc finger proteins encoded in the fly genome (10,11). However, unlike vertebrates, several of these polydactyl C2H2 zinc finger protein family members [Su(Hw), Pita, Zipic, Zw5, CLAMP, and Opbp] have been shown to play roles in chromosomal architecture in flies, and it is likely that other members of this large protein family will have similar functions (12)(13)(14)(15)(16)(17). Moreover, like dCTCF, two of these zinc finger proteins, Su(Hw) and Pita, are components of boundaries in BX-C and are important in the proper regulation of the BX-C homeotic genes (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%